2015
DOI: 10.1016/j.jlumin.2014.11.035
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of defects in cuprous oxide through exciton luminescence imaging

Abstract: The various decay mechanisms of excitons in cuprous oxide (Cu 2 O) are highly sensitive to defects which can relax selection rules. Here we report cryogenic hyperspectral imaging of exciton luminescence from cuprous oxide crystals grown via the floating zone method showing the samples have few defects. Some locations, however, show strain splitting of the 1s orthoexciton triplet polariton luminescence. Strain is reduced by annealing. In addition, annealing causes annihilation of oxygen and copper vacancies, wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 48 publications
3
15
0
Order By: Relevance
“…We speculate that the origin of these peaks is due to different trace impurities to those found in the Kyoto samples. We have also recorded the intensity of the PL emission at three discrete wavelengths known to be associated with copper and oxygen vacancies [45,48] in both synthetic and natural samples ( Fig. 7(a)).…”
Section: E Photoluminescence Spectroscopymentioning
confidence: 99%
“…We speculate that the origin of these peaks is due to different trace impurities to those found in the Kyoto samples. We have also recorded the intensity of the PL emission at three discrete wavelengths known to be associated with copper and oxygen vacancies [45,48] in both synthetic and natural samples ( Fig. 7(a)).…”
Section: E Photoluminescence Spectroscopymentioning
confidence: 99%
“…While cupric oxide inclusions can ultimately be removed in thin slices through annealing procedures, bulk single crystals larger than 1mm thick that do not contain macroscopic defects are still difficult to obtain. Inclusions are opaque and can induce strain [35, 36] in bulk crystals; they may be undesirable based on the intended applications.…”
Section: Introductionmentioning
confidence: 99%
“…However, most photoluminescence measurement techniques cannot locally measure the individual layers and interfaces within a bulk film device. Frazer et al has reported luminescence imaging excited by laser beam in Cu 2 O crystals fabricated by a floating zone method, and then related the luminescence imaging to lattice defects . The mapping obtained here was a region with a size of a few hundred micrometers.…”
Section: Introductionmentioning
confidence: 70%
“…It has been reported that lattice defects such as vacancies and impurities affect photoluminescence and photovoltaic properties of semiconductor materials and devices . Furthermore, localization of photovoltaic properties which is caused by their segregation and deficiency has been pointed out in multi‐layered film semiconductor devices.…”
Section: Introductionmentioning
confidence: 99%